Application of Appropriate Technology in Processing Coconut Coir Waste into Cocopeat to Increase the Value Added of Coconut Waste in Rejosari Village - Wiraguna, Rayie Tariaranie; Ihwanudin, M.; Anugrahani, Inanda Shinta; Azizah, Safira Rusyda; Putri, Helen Atris Romadhona Kuswandi; Cahyaningrum, Maurelin Azizah; Ulfa, Safinah Mufidah (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: Increase the added value of coconut fiber waste in Rejosari village by processing waste using appropriate technology into cocopeat products. Method: This service activity uses the Participatory Rural Appraisal (PRA) Model method, Participatory Technology Development Model, Community Development Model and Education in the implementation of its activities. Practical Application: The use of appropriate technology is expected to facilitate the processing of coconut coir waste into cocopeat. This technology can help process coconut fiber into fine granules in a short time. Conclusion: The application of appropriate technology in processing coconut coir waste into cocopeat can increase the value of the waste which was initially less than optimal. The processing of coconut fiber waste into cocopeat is expected to increase the income of the Rejosari Village community.